Analisis Peran Sektor Pertanian Di Perekonomian Wilayah Kota Tebing Tinggi - Safirah, Afza; Salqaura, Siti Sabrina (Universitas Medan Area, 2024)
Effective and efficient development planning is carried out if you know the potential of each region. This research aims to find out and analyze the basic sectors and subsectors for development in Tebing Tinggi City, there are 17 sectors used according to business fields in the 2017-2021 GRDP. This research was conducted in Tebing Tinggi City and the data was obtained from the Central Statistics Agency for Tebing Tinggi City and North Sumatra Province. This research uses a qualitative, descriptive approach. This research uses three analyses, namely Location Quotient (LQ) analysis, Dynamic Location Quotient (DLQ) analysis, and Klassen Typology. Based on the results of research on the agricultural sector in Tebing Tinggi City, non-based in the present and based in the future, however based on the Klassen Typology the agricultural sector is in the mainstay sector, namely LQ 1 and DLQ 1. In the future, each regional government must be able to maintain the stability of growth in each sector, both sectors base or non-base, because the base sector is the strength and competitiveness of the region and improves the regional economy.